Physiological response of citrus rootstocks seeds submitted to osmotic conditioning - Dias, Maristela Aparecida; Zucoloto, Moises; Dias, Denise Cunha Fernades dos Santos; Sediyama, Camilla Atsumi Zanuncio; Pereira da Silva, Danielle Fabiola; Neto, José Dias de Souza (Comunicata Scientiae, 2012)
Citrus rootstocks are propagated by seeds, which exhibit slow and irregular germination. Priming isone of the recommended techniques for uniform germination, and is characterized by seed presoakingin osmotic solution under certain temperature and time in order to restrict the amount ofwater absorbed. The work objective to evaluate the behavior of seeds of rootstocks, ‘Cleopatra’,‘Citrandarim’, ‘Sunki’, ‘Carrizo’, Gillyflower, Swingle, ‘Volkameriano‘, ’Citradia‘ and ’Rangpur’primed in osmotic solution containing PEG 6000 -0.8 and -1.2 MPa/48h; KNO3 0.34 M/48h; H2O/16hand unconditioned seeds, which were used as control. Analyses were carried out with completelyrandomized in factorial scheme (nine rootstocks X 5 conditioning treatments) with four replicationsof 50 seeds. The data were subjected to analysis of variance and means compared by Tukey’s testat 5%. Results indicated a differential response of varieties of rootstock in relation to conditioningtreatments applied with beneficial results for the Cravo cultivar, which comes out the other, beingfavored by conditioning in water and PEG -1.2 MPa, the range ‘Carrizo’ treated with PEG -1.2 MPaand the ‘Swingle’ conditioning in water is the most favorable for germination. For Rangpur cultivarconditioning in water, KNO3 and PEG -0.8 MPa exert similar beneficial effect.